Focus on Grammar 4/Marjorie Fuchs - Fuchs, Marjorie (United state of America: Pearson, 2012)
Trata de un conjunto de reglas implícitas que estructuran el uso del idioma inglés.
1.Present and Past 2.Future 3.Negative
incluye índice
Col. Educ
Keywords: 1.GERUNDS AND INFINITIVES 2.PHRASAL VERBS 3.ADJECTIVE CLAUSES